PRINSIP DAN SYARAT PENJATUHAN HUKUMAN BAGI ANAK BERKONFLIK HUKUM - Rasdianah Rasdianah (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2017)
The principle of imposing the punishment of a child of the perpetrator of a crime so that there is a reason for the criminal sanction to qualify for forgiveness, also the enactment of two forms of punishment (acts and criminal) for a child in conflict law is a further embodiment of the three punishment principles recognized in UUSPPA, namely the principle of criminal liability, the best interes of the child and ultimum remidium principle. The three principles of punishment also form the foundation of UUSPPA formers so that there are two conditions of punishment for children in conflict law, namely the absolute punishment requirements and relative condemnation requirements.Keywords: Principle of Punishment, Punishment Requirement, Child Conflict Law Prinsip penjatuhan hukuman bagi anak pelaku tindak pidana sehingga terdapat alasan penghapus pidana berkualifikasi alasan pemaaf, juga diberlakukannya dua bentuk hukuman (tindakan dan pidana) bagi anak berkonflik hukum merupakan perwujudan lebih lanjut dari tiga prinsip penghukuman yang diakui dalam UUSPPA, yaitu prinsip pertanggungjawaban pidana, prinsip the best interes of the child dan prinsip ultimum remidium. Ketiga prinsip penghukuman tersebut juga menjadi landasan dari pembentuk UUSPPA sehingga diberlakukan dua syarat penghukuman bagi anak berkonflik hukum, yaitu syarat penghukuman absolut dan syarat penghukuman relatif.Kata Kunci: Prinsip Penjatuhan Hukuman, Syarat Penjatuhan Hukuman, Anak Berkonflik Hukum